Human Resource Development Human Resource Management to Increase Job Satisfaction - Zahroh, Fatimatus; Cindy Safvitri; Ismail Iriani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine human resource management to increase job satisfaction with the performance of public works employees at PT Anima Tour & Travel Umrah, Surabaya Regency. This research is quantitative research because the approach used is for research proposals, processes, going to the field, company interviews, data conclusions and the content of the interviews. The subjects of this research were public works employees at PT Anima Tour & Travel, Surabaya City. This company has a branch and its head is located in Gresik. This research is all employees at PT Anima Tour & Travel in the city of Surabaya, numbering quite a lot of employees, more than 10 employees, showing that job satisfaction does not have an effect on employee work